Antimicrobial drug usage from birth to 180 days of age in Irish dairy calves and in suckler beef calves. Issue 1 (1st January 2019) - Earley, B.; Arguello, A.; O'Riordan, E.; Crosson, P.; Cappelleri, A.; McGee, M.
ABSTRACT: Concern about the use of antimicrobials in food producing animals is increasing. The study objective was to quantify antimicrobial drug usage in calves using antimicrobial treatment records from Irish suckler beef and dairy farms. Antimicrobial treatment records for calves born between 1 July 2014 and 30 June 2015 on 79 suckler beef and 44 dairy farms were analyzed. Calves were followed from birth (day 0) until 6 months of age. According to standard farm protocol, calves exhibiting clinical signs of any disease were identified and antimicrobial treatment was administered. Farmers recorded the following information for each treatment administered: calf identification, age at treatment, disease event, drug name, number of treatment days, and amount of drug administered. In total, 3, 204 suckler beef calves and 5, 358 dairy calves, representing 540, 953 and 579, 997 calf-days at risk, respectively, were included in the study. A total of 1, 770 antimicrobial treatments were administered to suckler beef ( n  = 841) and dairy calves ( n  = 929) between birth and 6 months of age. There was large variation in TIDDDvet and TIDCDvet by farm. This study provides new insights into the time periods and indications for which specific antimicrobial substances are used in Irish dairy and beef suckler calves.